Nucleation of the electroactive β-phase, dielectric and magnetic response of poly(vinylidene fluoride) composites with Fe2O3 nanoparticles - Gonçalves, Renato Ferreira (2013)
Iron oxide magnetic nanoparticles (IOMNPs) with average size of ~ 15 nm, synthesized by a co-precipitation technique were included in a poly(vinylidene fluoride) (PVDF) matrix with the objective to produce IOMNPs/PVDF multiferroic nanocomposites by solvent casting and melt processing. Increasing concentration of the IOMNPs nucleates the piezoelectric β-phase of the polymer, decreases the degree of crystallinity and increases the melting temperature of the polymer matrix leading to electroactive materials with large potential for sensor and actuator applications. The macroscopic magnetic and dielectric response of the composites depends on the weight fraction of IOMNPs nanoparticles in the nanocomposite, with both magnetization and dielectric constant increasing for increasing filler content. A typical superparamagnetic behavior was observed in the IOMNPs /PVDF composites.